UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DENGAN MENGGUNAKAN METODE PROJECT BASED LEARNING - Maria Angela Dora Kelen; Noviana Boleng Lamarobek (CV. Adiba Aisha Amira, 2025)
This study aims to improve the learning outcomes of class VIII B students at SMP Negeri 1 Solor Barat on the material of the Mission of Jesus' Disciples by using the project based learning method. At SMP Negeri 1 Solor Barat, it is illustrated that the learning outcomes obtained by class VIII B students in the material of the Mission of Jesus' Disciples are still very low because there are students who have not met the minimum completion criteria (KKM). The low learning outcomes of Catholic religious education are caused by the selection of inappropriate teaching methods. So that students are not enthusiastic in participating in learning. The method used in this study is classroom action research (CAR). Classroom action research is research conducted in the classroom by teachers to fix problems in the classroom with the aim of making changes. The results show that the use of the project based learning method in Catholic religious education learning can improve the learning outcomes of class VIII B students. Where this is indicated by the average class value of each cycle, namely pre-cycle (59.56) while cycle I (80) and in cycle II (84.21). This shows that the use of the project based learning method can improve the learning outcomes of class VIII B students at SMP Negeri 1 Solor Barat.